Knowledge, Attitude and Perception Towards COVID-19 Appropriate Behaviour in South India on General Public - Suresh, Chenchu; Lahari, Veluri; Kumar, Jinkala Suneel; Rushitha, Madamanchi; Sharon, Bhaktula Pretty (Journal of Neonatal Surgery, 2025)
The global pandemic of the Coronavirus illness (COVID-19) is creating unprecedented levels of morbidity and mortality. In an effort to alleviate the burden on healthcare systems and flatten the curve, the majority of nations throughout the world have implemented emergency lockdown. The objective of the study to evaluate the basic knowledge, attitude, and perception among the rural and urban Indian population toward the ongoing COVID ‑19 pandemic and to assess the understand the practices of appropriate behaviour among the general public. Methodology: This study was questionnaire-based descriptive cross‑sectional study conducted online. Compilation and assessment of the online data in the form of responses were done as for descriptive studies. A total of 520 responses were collected by using google forms, belonged to urban areas and rural areas. Results: Most of them (92.9%) respondent's perceived that early detection will have a better outcome from COVID-19. The assessment of the parameter attitude, 89% (462) of the participants believe that controlling the spread of infection is a successful strategy, and 74.9% (389) are confident that COVID-19 can be successfully controlled. The evaluation of the COVID-19 practices revealed that, of the total respondents, 94.8% (492) wear masks when going outside, 82.2% (430) wash their hands with soap or sanitizer, 88.8% (461) in recent days from touch your hands, mouth, nose and eyes frequently 87.2% (453) of respondents frequently maintain social distance in public places. Conclusion: It was reported wide gap exists between urban and rural population related to COVID awareness and COVID Appropriate Behaviour. Most of the rural participants had poor Knowledge on appropriate behaviour on Covid-19. Most urban participants know the four most effective preventive behaviours, as wearing mask, washing hand with soap and water and avoiding crowded place or maintaining social distance In order to improve the public's understanding of COVID-19 and encourage adherence to health protocols, masking, hand hygiene, social distancing, and vaccination to prevent expected COVID-19 subsequent episodes, the government and private agencies should continue their consistent efforts to change the public's negative behavioural attitude to positive behaviour.